Employee Health and Firm Performance - Daniel A. Rettl; Alexander Schandlbauer; Mircea Trandafir (Institute of Labor Economics (IZA), 2022)
When workers are in bad health, their productivity declines. We investigate whether the health of employees affects firm performance, taking advantage of the severity of the seasonal influenza seasons as a source of exogenous variation. We find that firms whose employees are particularly affected by influenza experience reductions in their return on assets and in net income. These results are not driven by firm-specific characteristics, as we find the same relationship between influenza severity and firm performance within firms, at the establishment level. We also document substantial heterogeneity in the effects, with small firms and labor-intensive firms driving our findings. This suggests that labor is an important driver of firm performance and that capital-intensive and larger firms are better able to shift resources in response to temporary shocks to their workforce. Back-of-the-envelope calculations suggest that smaller firms may be better off subsidizing vaccination programs for their employees.
Keywords: L25; I12; G30; J31; 330; seasonal influenza; health shock; firm performance